ChemInform Abstract: Chiral Phosphoramide‐Catalyzed Enantioselective Synthesis of 2, 3′‐Diindolylarylmethanes from Indol‐2‐yl Carbinols and Indoles. Issue 1 (January 2015) - Qi, Shuai; Liu, Chao‐You; Ding, Jin‐Ying; Han, Fu‐She
Abstract The first asymmetric addition of indol carbinols (I) with indol derivatives (II) and (IV) catalyzed by a BINOL‐derived phosphoramide affords title compounds (III) and (V) in high yields as well as high enantioselectivities.